2014
DOI: 10.1055/s-0034-1364940
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetic countertraction device for endoscopic submucosal dissection significantly reduces procedure time and minimizes technical difficulty

Abstract: Background and study aims In endoscopic submucosal dissection (ESD), effective countertraction may overcome the current drawbacks of longer procedure times and increased technical demands. The objective of this study was to compare the efficacy of ESD using a novel magnetic countertraction device with that of the traditional technique. Methods Each ESD was performed on simulated gastric lesions of 30mm diameter created at five different locations. In total, 10 ESDs were performed using this novel device and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…1a ). There is only one study focused on comparing MG-ESD and conventional ESD, which found results similar to ours 8 . Unfortunately, the authors did not include information on any outcomes concerning adverse events.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…1a ). There is only one study focused on comparing MG-ESD and conventional ESD, which found results similar to ours 8 . Unfortunately, the authors did not include information on any outcomes concerning adverse events.…”
Section: Discussionsupporting
confidence: 81%
“…Despite these promising preliminary results, there is only one comparative study in an ex vivo gastric model, of conventional ESD (ESD) versus MG-ESD. This study shows how MG-ESD is more efficient than ESD, and equivalent in terms of safety 8 . On the other hand, waterjet-assisted ESD consists of pressure-controlled injection of fluids through the tip of a waterjet knife.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several traction methods for ESD have been investigated to overcome the problem, such as percutaneous traction [ 5 ], clip with line [ 6 8 ], clip-and-snare [ 9 ], external grasping forceps [ 10 ], internal traction [ 11 , 12 ], suture-pulley [ 13 ], magnetic anchor [ 14 ], double-channel endoscope [ 15 ], double-endoscope [ 16 ], and robot-assisted method [ 17 ]. However, those traction methods need extra devices or equipment and may be invasive or difficult to control the pulley strength and direction or inconvenient to be operated.…”
Section: Introductionmentioning
confidence: 99%
“…A thin intestinal muscle layer, poor endoscopic operability and submucosal visual field insufficiency will all increase the risk of complications [1,2]. Magnetic anchor guided ESD (MAG-ESD) provides adequate direction and degrees of traction in various locations, which effectively improves the surgical field of vision [3,4].…”
mentioning
confidence: 99%